Effect of food-based strategies of Iranian traditional medicine on women's quality of life during menopause - Maryam Shahraeini; Nahid Jahani shourab; Roghaye Javan; Mohamad Taghi shakeri (Mashhad University of Medical Sciences, 2021)
Introduction: The complication caused by estrogen deprivation during menopause has negative effects on women's quality of life. The use of food-based strategies based on Iranian traditional medicine is one of the suggested strategies to relieve menopausal sign and symptoms and finally improves their quality of life. Therefore, this study was performed with aim to determine the effect of food-based strategies based on Iranian traditional medicine on women's quality of life during menopause. Methods: This two-group clinical trial study was performed on 57 postmenopausal women in 2018. Two health comprehensive service centers of Chardah-Masoum and Imam Hassan were randomly selected from health center (No 2) as the intervention and control group, respectively. Then, the eligible women were sampled by convenience. In the intervention group, food-based strategies of Iranian medicine were educated in three sessions of 60-90 minutes during 3 week. The control group received routine care of the health center. Two groups were followed up for 2 monthsin adherence to orders. Data was collected through Menopause Specific Quality of Life Questionnaire (MENQOL), Beck Anxiety and Depression Inventory and Mizaj questionnaire. Data were analyzed by SPSS software (version 16) and independent t-test, Chi-square, Mann-Whitney, and Wilcoxon tests. p < 0.05 was considered statistically significant. Results: There was no statistically significant difference between quality of life, depression, anxiety and mizaj of women in the two groups before the intervention (p>0.05). But after the intervention, decreased scores showed an improvement in quality of life and depression in the intervention than the control groups (p <0.001). Conclusion: The use of food-based strategies increases the quality of life in menopausal women. So, it is suggested for management of the signs of menopause.